2014
DOI: 10.1111/cns.12279
|View full text |Cite
|
Sign up to set email alerts
|

Procognitive Properties of Drugs with Single and Multitargeting H3 Receptor Antagonist Activities

Abstract: The histamine H3 receptor (H3 R) is an important modulator of numerous central control mechanisms. Novel lead optimizations for H3 R antagonists/inverse agonists involved studies of structure-activity relationships, cross-affinities, and pharmacokinetic properties of promising ligands. Blockade of inhibitory histamine H3 autoreceptors reinforces histaminergic transmission, while antagonism of H3 heteroreceptors accelerates the corticolimbic liberation of acetylcholine, norepinephrine, glutamate, dopamine, sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 138 publications
1
21
0
2
Order By: Relevance
“…These preclinical observations suggested that pitolisant is a valuable drug candidate to be developed in wakefulness or memory deficits and other cognitive disorders [52,107]. Notably, pitolisant showed in doses up to 20 mg/day procognitive effects in patients with this condition, suggesting that H3R antagonists are of therapeutic value in conditions associated with memory impairment [108].…”
Section: Alzheimer's Diseasementioning
confidence: 97%
See 2 more Smart Citations
“…These preclinical observations suggested that pitolisant is a valuable drug candidate to be developed in wakefulness or memory deficits and other cognitive disorders [52,107]. Notably, pitolisant showed in doses up to 20 mg/day procognitive effects in patients with this condition, suggesting that H3R antagonists are of therapeutic value in conditions associated with memory impairment [108].…”
Section: Alzheimer's Diseasementioning
confidence: 97%
“…Interestingly, results observed in preclinical experiments showed that the H3R antagonist DL-77, a compound structurally strongly related to pitolisant, improves cognitive performance through actions on different memory stages, demonstrating the possible implication of H3Rs for the treatment of neuropsychiatric disorders associated with cognitive symptoms emerging with the chronic use of antiepileptic drugs [109]. PF-03654746 is a potent H3R antagonist and was found to be effective in several experimental object recognition models ( Figure 10, Table 1) [52,106,107]. Moreover, PF-03654746 recently completed a phase 2 study evaluating its efficacy on excessive day-sleepiness associated with narcolepsy with proved efficacy observed in two drug groups versus placebo (ClinicalTrials.gov trial registration number: NCT01006122).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Theinitial, reversible inhibition of MAO A/B (reflecting binding) and inhibition after 30 min preincubation of the inhibitor with the enzymes (because of irreversible inhibition) were determined (Table 1). [17,20,21] As compounds 6 and 7 exhibit comparable H3R affinity,w eh ave demonstrated that the H3R affinity is positively influenced by the introduction of the second basic moiety,t he propargylamine motif,w hich is responsible for MAOi nactivation. After preincubation, the IC 50 values shifted to nanomolar concentrations for most of the propargylamines.T he irreversibility of the MAOi nhibition was confirmed for contilisant by 50-fold dilution into excess substrate.T he IC 50 value for compound 6 changed very little with preincubation, suggesting that the propargyl group did not form ac ovalent adduct with MAOB .C ompound 7,l acking the propargyl group, showed no change with preincubation.…”
mentioning
confidence: 98%
“…These abovementioned aspects of H 3 R suggest that this receptor subtype is much more than just an auto-receptor altering histaminergic neurotransmission. Therefore, a broad interest within the pharmaceutical industry has been instigated to develop specific H 3 R antagonists for the treatment of sleep-wake disorders, obesity (histamine-dependent), and attention and cognitive deficits (noradrenaline-and acetylcholinedependent) in preclinical and clinical phases [19][20][21][22][23][24][25]. Despite the aforementioned findings supporting the role for H 3 Rs in the modulation of alcohol-related behaviors, targeting the brain histaminergic system is not commonly listed as a future strategy to approach treating alcoholism.…”
Section: Introductionmentioning
confidence: 99%